Analisis Ancaman Kejahatan Siber Bagi Keamanan Nasional Pada Masa Pandemi COVID-19 - Amarullah, Abdul Hanief; Runturambi, Arthur Josias Simon; Widiawan, Bondan (Jurnal Kajian Stratejik Ketahanan Nasional, 2021)
COVID-19, a new variant of pneumonia had the ability to spread rapidly. The resulting impact of the rapid spread of the virus can be seen in all parts of the world. One of them is the change of behavior where face-toface activities are now held online, which has an impact on the increase of internet usage, also the increase of cybercrime threats. This research aims to determine the level of threat of cybercrime that occurred during the COVID-19 pandemic, as well as the role of the Indonesian government in identifying and mitigating it. Data on cybercrime and key events used is data from February through April of 2020, obtained from various open sources. Timeline analysis is used on cybercrime and key events data to help make identifying cybercrime easier before a threat analysis is performed. Cybercrimes that occur during time of research can be categorized into 4 (four) threat agents; malware, online fraud, Zoombombing, and Distributed Denial-of-Service (DDoS). Malware becomes the majority of threat agent, and after the threat analysis is performed, belongs to ‘critical’ level, while online fraud and DDoS fall into the ‘high’ level and zoombombing falls into ‘negligible’ level. Government agencies responsible for detecting and mitigating cyber crime threats are the National Cyber and Crypto Agency, State Intelligence Agency, and Indonesian National Police. Keywords: COVID-19, cybercrime, threat analysis